REKONSTRUKSI EPISTEMOLOGI PEMIKIRAN POLITIK ISLAM INDONESIA KONTEMPORER - Azhar, Muhammad (Universitas Muhammadiyah Surakarta, 2015)
The thought of Islamic politics which develops in Indonesia recently has various epistemology, either being viewed from the discourse of Islamic politics conveyed by Muslim politicians, or what contained on the basic stipulation/bylaws (AD/ART) of each party. It is a kind of plurality of Islamic political thought which is less influenced by the frame of Islamic political epistemology itself and by Islamic political paradigm which develops in Indonesia that has textual-idealistic, realistic and integral patterns. To further investigate the problem, the focus of this research was how is an ideal reconstruction of the contemporary thought of Indonesian Islamic politics? The results of the research showed that the epistemology frame of Islamic political thought that has classical and mid century pattern should be reconstructed suitable with the context of social life of 21st century, in which the interaction among Muslim community or non Muslim community has been closer each other. Of course, it needs a new theology of Islamic politics which is more tolerant and pluralistic, therefore, issues of contemporary politics related to the concept of hudûd, gender problem, muslim-non muslim positions, concept of dãrulharb, human rights, citizenship, a new relation pattern between Islam and the West, response of political philosophy on postmodernism and other issues can be responded and implemented according to the principle of Islamic politics.